Dominant Anthropocentrism in the Representations of Nature in The Jakarta Post “Destinations” Travel Articles (Hiski Malang, 2021)
In the light of the critique of tourism for its potential harms to nature and communities, travel article might contribute to the harm in one way or another. This essay covers a study on thirty travel articles published in the “Destinations” section of The Jakarta Post from September to December 2017. The articles were analyzed for words, sentences, or passages that in one way or another represent nature. The purpose of this study was to explore and explain how travel articles represent nature and, by extension, to demonstrate how today’s travel articles might contribute to the potentially damaging impact of tourism on nature. From this study, I discovered that there are seven ways in which writers represent nature in the studied texts. These ways include representations that focus on 1) spirituality, 2) visual beauty, 3) celebration of popular culture, 4) social media presence, 5) mental rejuvenation, 6) prudent treatment of nature, and 7) concern for preservation. These seven ways of representation fall into three tendencies in the representation of nature, i.e. 1) full anthropocentrism, 2) thoughtful anthropocentrism, and 3) relative ecocentrism. The high percentage of representations of nature in the first category arguably supports the criticism of tourism. In the final analysis, I argue that travel article contributes despite relatively small to the imminent threat of tourism industry.